A Mobile Personal Finance Application People Spend Money And Provide Intelligent Saving Advice With The Assistance Of AI. - Ramala T, Ramala T; H, Yogeshwaran; Rl, Tharun (Journal of Neonatal Surgery, 2025)
Personal financial management has continued to be a significant issue in contemporary digital lives because of unorganized cost monitoring and analytic support. These adversities generally cause imprudent spending and low saving habits. To overcome these issues, the given research paper describes a personal finance management system that can be run as a mobile application to investigate the spending habits and provide intelligent information on saving based on the data learning methods. The development is implemented as an Android-based application with the help of Flutter and Dart, which guarantees a seamless interaction and a smooth performance with different devices. Protective authentication can be used to allow individuals access to financial records. The monthly income data is registered and sensibly distributed among the previously established categories of expenses such as food, shelter, transport, recreation and savings. The daily monetary entries are checked on a daily basis and dynamic visual notification of the category-based budget violation is used to promote disciplined financial behavior. The analysis of spending behavior is carried out by taking historical records of monthly expenses and processed in a trained learning model. Structured datasets are used to train and evaluate models and performance is determined using classification metrics. According to experimental results, the suggested analytical framework is accurate with 92.4% accuracy, whereas the applied prediction model incorporated in the application has 90.1% accuracy in the real usage conditions. According to classification findings, tailor-made savings consultations are provided to improve financial consciousness. Generally, the given research paper provides a witty, effective, and scalable platform of sustainable personal finance planning by the means of predictive analytics and behavioral data..